The hepatic-portal vein in rabbits of White New Zeland bredd (Oryctolagus cuniculus Linnaeus, 1758) - Birck, Arlei José; Miglino, Maria Angelica; Machado, Gilberto Valente; Santos, Tatiana Carlesso dos (Brazilian Journal of Veterinary Research and Animal Science, 2006)
Considering the shortage of information in the literature, it is looked for to draw a profile of formation of the portal vein in twenty rabbits, to recognize the distribution pattern, looking for evidences of possible correlation between the formation patterns and the distribution of the portal vein. The animals were injected by Neoprene latex, fixed in formalin 10% and dissected. The hepatic-portal vein, in it extraparenquimal trajectory, was constituted, for the junction of the cranial and caudal mesenteric veins and receives veins from the stomach, spleen and pancreas. The cranial mesenteric vein receives, in all cases, a jejunal and an ileocecocolic trunk. The jejunal trunk was formed by the junction from eight to eighteen jejunal veins. The ileocecocolic trunk was formed by the encounter of the colic, cecals and ileal veins, in different arranjements and numbers. The caudal mesenteric vein was formed by junction of the rectal and left colic veins.